Medical cannabis: aligning use to evidence‐based medicine approach. (28th August 2018) - Bar‐Lev Schleider, Lihi; Abuhasira, Ran; Novack, Victor
Abstract: During the past decade we have been witnessing a rise in medical cannabis use, yet the evidence for the safety and efficacy of the various cannabinoid compounds is scarce. The State of Israel has always been at the forefront of clinical and translational research in support of Evidence Based Medicine. With respect to cannabis Israel has created a medical and regulatory environment that enables clinical studies with cannabis which may lead to improved Evidence Based use of these compounds. This opinion paper discusses selected studies into the safety and effects of cannabis derived products.